Pool of Resistance Mechanisms to Glyphosate in Digitaria insularis - de Carvalho, Leonardo Bianco [UNESP]; da Costa Aguiar Alves, Pedro Luis [UNESP]; Gonzalez-Torralva, Fidel; Enrique Cruz-Hipolito, Hugo; Maria Rojano-Delgado, Antonia; De Prado, Rafael; Gil-Humanes, Javier; Barro, Francisco; Luque de Castro, Maria Dolores (Amer Chemical Soc, 2012)
Digitaria insularis biotypes resistant to glyphosate have been detected in Brazil. Studies were carried out in controlled conditions to determine the role of absorption, translocation, metabolism, and gene mutation as mechanisms of glyphosate resistance in D. insularis. The susceptible biotype absorbed at least 12% more C-14-glyphosate up to 48 h after treatment (HAT) than resistant biotypes. High differential C-14-glyphosate translocation was observed at 12 HAT, so that >70% of the absorbed herbicide remained in the treated leaf in resistant biotypes, whereas 42% remained in the susceptible biotype at 96 HAT. Glyphosate was degraded to aminomethylphosphonic acid (AMPA), glyoxylate, and sarcosine by >90% in resistant biotypes, whereas a small amount of herbicide (up to 11%) was degraded by the susceptible biotype up to 168 HAT. Two amino acid changes were found at positions 182 and 310 in EPSPS, consisting of a proline to threonine and a tyrosine to cysteine substitution, respectively, in resistant biotypes. Therefore, absorption, translocation, metabolism, and gene mutation play an important role in the D. insularis glyphosate resistance.
Keywords: N-phosphonomethylglycine; EPSPS; weed resistance; mechanisms of resistance; sourgrass